Structured image diagnosis of vertebral body degeneration and disc damage - Binary image criteria and comparison for systematic image analysis in occupational diseases 2108/2110. - Braunschweig, Rainer; Kildal, Daniela; Meyer-Clement, Michael; Janka, Rolf Matthias; Tiemann, Andreas (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
BACKGROUND: Occupationally related limitations of earning capacity can be recognized under social legislation and may be subject to compensation ("reduction in earning capacity"). For this purpose, legislators have defined a list of occupational diseases ("BK list"). Recognition of an occupational disease requires a legal assessment procedure based on a medical appraisal. The aim of the assessment is to prove the "causality" and the "causality giving rise to liability". METHOD: In addition to clinical findings and workplace analyses, imaging methods (projection radiography, MRI) are primarily used to substantiate liability. These methods enable proof of load-conforming damage patterns for occupational diseases 2108/2110 (damage to intervertebral discs). RESULTS AND CONCLUSION: In addition to the legal background, the following review article primarily presents the image criteria for load-conforming damage patterns of the spine. On the basis of the consensus paper on the "Assessment of occupational disc diseases of the lumbar spine", image criteria are assigned to age-atypical grades of findings, and "typical constellations of findings" are defined for vibration (BK 2108) or lifting (BK 2110) loads. The aim of Part 1 is to explain the image criteria of the comparative images presented as image plates in Part 2 and thus to present a reference catalog of findings. KEY STATEMENTS: · Occupational diseases are defined by legislators in the "List of Occupational Diseases".. · For occupational intervertebral disc diseases (BK 2108/2110), constellations of findings are defined.. · In the context of imaging diagnostics, a large number of image criteria are used.. · Part 1 explains the basics.. · Part 2 provides the image criteria on the basis of "comparative images" as a reference catalog.. CITATION FORMAT: · Braunschweig R, Kildal D, Meyer-Clement M et al. Structured image diagnosis of vertebral body degeneration and disc damage - Binary image criteria and comparison for systematic image analysis in occupational diseases 2108/2110. Fortschr Röntgenstr 2024; 196: 347 - 353.
EVALuna2:557959
Keywords: occupational diseases; degenerative spine conditions; structured image diagnosis; intervertebral disc degeneration; systematic medical image analysis